Variation of aerosol optical thickness with atmospheric water vapour : A case study over a continental station Mysore, India - GANESH, K.E.; UMESH, T.K.; NARASIMHAMURTHY, B. (MAUSAM, 2011)
Atmospheric measurements in a continental, low latitude station Mysore (12.3° N) has been carried out, for the period December 2003 to June 2006. Measurements were made using a sunphotometer with five bands in the visible and near-infrared range of the solar spectrum. To bring out the wavelength dependence of Aerosol Optical Thickness (AOT) on atmospheric water vapour, typically two wavelength channels are being used, one at 500 nm and the other at 1020 nm. A linear dependence between AOT and water vapour on meteorologically calm days is the important observation made. Growth rate of AOT is found to be larger at shorter wavelength (500 nm) than that of the longer wavelength (1020 nm). A mass-plot representation is followed on monthly basis, which is nothing but the graphical plot of spectral AOT versus water vapour of the scans for all the clear sky days of a particular month. Further investigations reveal that some months exhibit a single trend of growth of AOT with water vapour whereas double trend is the scenario for other months. These results provide insight into the changes in the atmospheric aerosol characteristics with precipitable water vapour, which is the subject matter of this paper.